Impact of Surface Functionalization on the Intrinsic Properties of the Resulting Fe–N–C Catalysts for Fuel Cell Applications. Issue 9 (4th September 2020) - Kübler, Markus; Wagner, Stephan; Jurzinsky, Tilman; Paul, Stephen; Weidler, Natascha; Gomez Villa, Eduardo D.; Cremers, Carsten; Kramm, Ulrike I.
Abstract : Carbon nanotubes (CNTs) are corrosion resistant supports for electrochemical applications. A surface functionalization of CNTs prior to pyrolysis enables improved interaction with carbon frames hosting FeN4 moieties: higher site densities and turn‐over frequencies are reached. Together with the good cycling stability during accelerated stress tests, this makes Fe–N–C catalysts of interest for integration in proton‐exchange fuel cells (PEFCs). More details can be found in article number 2000433 by Ulrike I. Kramm and co‐workers.